SURVEYS AND OIL POLLUTION IN THE ASEAN COUNTERIES - Jaspar Billal (Scientific Contributions Oil and Gas, 1987)
The Sourheast Aslan Seas it a region having valuable and vulneruble marine and coattul resources and sinuated along denaely shipping router and oil uctiviries.            The concerm of the coastal countries in the repion on marine oil pollution has been pointed out in uriout regional meetings.            Many researchen and their institution started to look on the level of the contaminarion The author tummartzer and compare all information available and expose the g of knowledge on the extent of oil contamination tn the region.            A Regional Cooperation for the asseument and enaluarion af ol polhution it needed and being exrablished to ennure and obtain a compatible data and meaningful regional innerpretarion,